Aging of the genome the dual role of DNA in life and death - Vijg, Jan. (Oxford : Oxford University Press, 2007)
Aging has long been ascribed to the gradual accumulation of mutations in the genome. However, it is only recently that the technology has been developed to test this theory and its consequences. This book reviews the concept of genomic instability as a possible universal cause of aging in complex organisms.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aging -- Genetic aspects; Apoptosis; Genomes; Developmental genetics; DNA damage